2023
DOI: 10.3390/toxics11060509
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anti-Alzheimer Pursuit of Jambolan Fruit Extract and/or Choline against AlCl3 Toxicity in Rats

Zeinab Abdel Salam Hawash,
Ensaf M. Yassien,
Badriyah S. Alotaibi
et al.

Abstract: Jambolan fruit extract and choline were investigated for Aluminum tri chloride (AlCl3)-induced Alzheimer’s disease in rats. Thirty-six male “Sprague Dawley” rats weighing (150 ± 10 g) were allocated into six groups; the first group was fed a baseline diet and served as a negative control. Alzheimer’s disease (AD) was induced in Group 2 rats by oral administration of AlCl3 (17 mg/kg body weight) dissolved in distilled water (served as a positive control). Rats in Group 3 were orally supplemented concomitantly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…This showed that flavonoids have AChE restoration properties. However, other studies [i.e., Thangarajan et al (2018) administering Morin for 2 weeks; Akpa et al (2020) and Hawash et al (2023) administering fisetin for 7 weeks and Convolvulus pluricaulis 1 week, respectively] showed a negative effect, favoring control. In addition, six studies [mean difference (MD), −3.95 U/mg protein; 95%CI (−11.76, 3.87)] found a trend in flavonoids improving cognition through AChE but did not reach significance, with a heterogenicity of 99% between studies.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This showed that flavonoids have AChE restoration properties. However, other studies [i.e., Thangarajan et al (2018) administering Morin for 2 weeks; Akpa et al (2020) and Hawash et al (2023) administering fisetin for 7 weeks and Convolvulus pluricaulis 1 week, respectively] showed a negative effect, favoring control. In addition, six studies [mean difference (MD), −3.95 U/mg protein; 95%CI (−11.76, 3.87)] found a trend in flavonoids improving cognition through AChE but did not reach significance, with a heterogenicity of 99% between studies.…”
Section: Resultsmentioning
confidence: 87%
“…The statistical results demonstrated that flavonoid administration [nine studies; mean difference (MD), −1.98 nmol/mg protein; 95%CI (−3.20, −0.77)] has a significant effect in reducing MDA level among the animals with cognitive impairment as the effect favors experimental/intervention group, with a heterogenicity of 87% between studies. The nine studies included are as follows: Wu et al (2012) administered green tea extract (GTex), epigallocatechin gallate (EGCG), for 7 days; Jia et al (2016 ) administered liquiritin for 2 weeks; Mansour et al (2017 ) administered 5, 7-dihydroxyflavone for 3 weeks; Peter AN and Rehab AA 2021 administered hesperidin for 8 weeks; Kwon et al (2022 ) administered Rhodiola sachalinensis for 3 weeks; Hawash et al (2023 ) administered jambolan fruit ethanolic extract for 28 days; Jadhav and Kulkarni (2023 ) administered baicalein for 21 days and quercetin for 42 days, respectively; and finally, Kim et al (2023 ) administered Sesamum indicum L. for 4 weeks.…”
Section: Resultsmentioning
confidence: 99%